Geometrical and electronic structure of Pd clusters on graphite - Bovet, M.; Boschung, E.; Hayoz, J.; Pillo, Th.; Dietler, G.; Aebi, Philipp (My University, 2001)
Pd clusters formed by physical vapor deposition at room temperature (RT) on highly oriented pyrolytic graphite were investigated by a combination of X-ray photoelectron spectroscopy and diffraction, angle-resolved ultraviolet photoelectron spectroscopy, scanning tunneling microscopy and calculations based on the local density functional theory. Different coverages with nominally 3, 5 and 10 Å were studied after deposition at RT and after heat treatment at 600°C. Local ordering exhibiting growth with an fcc(1 1 1) orientation is already observed at the lowest coverage, but with no preferred azimuthal orientation in accordance with the substrate itself. However electronic structure features characteristic for a Pd(1 1 1) single crystal appear only after heat treatment.
Keywords: palladium; graphite; clusters; photoelectron diffraction; angle resolved photoemission; density functional calculations